A inclusão educacional do sujeito surdo: direito garantido ou reprimido? - Ruzza, Mara Lopes Figueira de (2016)
The appreciation of the subject Deafness and its culture, language, identity and Deaf Community requires a critical reading of the current context of Brazilian education and inclusion policies that are being implemented. Given the scientific and social relevance of this dissertation entitled " The Educational Inclusion of the Deaf Subject: guaranteed or repressed Right?" the research problem occurs by the complex relationship between the educational inclusion of the Deaf in regular schools and the lack of guarantee in its own right to be Subject Deafness. The overall objective of the research results from the contextualization of its problematic: Critically analyze the educational inclusion policy, checking the conditions in which the subject Surdo has its guaranteed rights or repressed. For discussion of topics such as subject Deafness and their differences, the right to education through the inclusive education and bilingual education for the Deaf, it was used as a conceptual theoretical basis of the research: Federal Constitution (1988), Dorziat (2011), The Person Statute with Disabilities (2015), Lodi and Lacerda (2009), Moura (2000), National Education Plan (2010), Pereira (2011), Quadros (1997 and 2004), Sá (2006), Skliar (1998 and 2003), Strobel (2008) and Vieira (2000). Guided in Severino reflections (2002) and Ludke and André (2013), the methodological options of this work were: mapping through a virtual questionnaire to 194 teachers of Municipal and State Public Schools in São Paulo with subsequent qualitative analysis and structured interviews with 12 teachers who had students in their regular classes Deaf. The data demonstrate that although there knowledge of current legislation and some aspects that underlie the constitution of the subject Deafness, there is no effective change in school practices so that the differences of the Deaf subject are considered. Therefore, as one of the final considerations of this research, it is clear that educational inclusion of deaf students in regular schools is characterized as a repressive state, not ensuring the full right to be Subject Deafness